Efforts to Improve Students' Learning Motivation by Implementing the Problem-Based Learning Model in Elementary Schools - Muhammad Nurul Huda; Nasyariah Siregar; Rusmanto Rusmanto (al-Afkar, Journal For Islamic Studies, 2026)
The purpose of this study is to find out how effective  the Problem-Based Learning (PBL) learning model, or problem-based learning, is in improving students' motivational learning ability to learn in grade IV of Natural and Social Sciences subjects at SD IT Asy-Syifa Al-Inayah 6 Jambi City. Using the Kemmis and McTaggart models, Classroom Action Research (PTK) is used, which includes steps of planning, implementation of actions, observation, and reflection. There were 19 students involved, and the data collection technique was carried out by looking at the activities of teachers and students as well as learning motivation questionnaires. The results were analyzed using quantitative and qualitative approaches. The results of the study show that the application of the problem-based learning  model is effective in increasing students' motivation to learn. This is shown by the increase in student activity from 55% in the pre-cycle to 68.33% in the first cycle and 83.33% in the second cycle, as well as the increase in the results of the motivational questionnaire from 53.18% in the first cycle to 69.40% in the second cycle.